Application of image processing for quantization and characterization of fabrics with polymeric coatings - YILDIZ, KAZIM; YILDIZ, ZEHRA (PAMUKKALE UNIV, 2018)
In this study, the dispersion quality of particles on polymeric coating formulations from cotton fabric surfaces was investigated by using gray level co-occurrence matrix and fractal dimension. Coating formulations with various nano particle inclusions were applied on cotton fabrics. The flame retardant property of coated fabrics were examined by thermal gravimetric analysis (TGA). Images from the coated fabric surfaces were obtained by using optical microscopy and then these images were used in gray level and fractal dimension feature extraction processes. The microscopic images of the coated fabrics in various particle amounts were analyzed by using the image processing technique, and then classification and quantization processes were performed. The results of the image processing were compared to the results of TGA. The sample containing 5% montmorillonite (MMT) was found as having the best coating quality level by using feature extraction method in image processing. The average classification performance among all the samples was found as 92.5%.
Keywords: Image processing; Fractal analysis; Cotton fabric; Polimeric cover; Nano particle; COTTON; ASSEMBLIES; LAYER